Romanisation and the problem of the Dardania substrate in Roman times - Mirdita, Zef (Balcanica Posnaniensia. Acta et studia, 1990)
The article addresses the problem of the romanization of Dardania and its impact on the indigenous population. The problem is significant for understanding the mechanisms of the Roman Empire’s influence on conquered regions. The aim of the work is to determine the scope and character of this process in political, social, economic, and cultural contexts. The author applies analysis of historical, epigraphic, and archaeological sources. The most important results indicate that romanization in Dardania was superficial and limited mainly to elites and administrative structures. Roman policy was based on pragmatism, including granting citizenship, developing urban centers, and tolerating local traditions and religions. At the same time, most of the population retained its own culture and legal status, which demonstrates the limited extent of integration. The conclusion is that romanization in Dardania was selective and did not lead to full assimilation of the local population.